2002
DOI: 10.1073/pnas.042693699
|View full text |Cite
|
Sign up to set email alerts
|

The brain-derived neurotrophic factor enhances synthesis of Arc in synaptoneurosomes

Abstract: Protein synthesis in neurons is essential for the consolidation of memory and for the stabilization of activity-dependent forms of synaptic plasticity such as long-term potentiation (LTP). Activitydependent translation of dendritically localized mRNAs has been proposed to be a critical source of new proteins necessary for synaptic change. mRNA for the activity-regulated cytoskeletal protein, Arc, is transcribed during LTP and learning, and disruption of its translation gives rise to deficits in both. We have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
192
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(200 citation statements)
references
References 58 publications
8
192
0
Order By: Relevance
“…In this context, it should be pointed out that activation of the translation machinery in dendrites may go hand in hand with the arrival of Arc transcripts, effectively driving Arc protein synthesis at synaptic sites (Ying et al, 2002). Supporting this view, BDNF has been shown recently to stimulate posttranscriptional synthesis of Arc in isolated synaptoneurosomes (Yin et al, 2002). This mechanism may well be accentuated in the context of elevated Arc mRNA.…”
Section: Discussionmentioning
confidence: 92%
“…In this context, it should be pointed out that activation of the translation machinery in dendrites may go hand in hand with the arrival of Arc transcripts, effectively driving Arc protein synthesis at synaptic sites (Ying et al, 2002). Supporting this view, BDNF has been shown recently to stimulate posttranscriptional synthesis of Arc in isolated synaptoneurosomes (Yin et al, 2002). This mechanism may well be accentuated in the context of elevated Arc mRNA.…”
Section: Discussionmentioning
confidence: 92%
“…BDNF promotes synaptic plasticity and synaptic consolidation that are dependent upon the transcription and translation of arc (Kang and Schuman 1996;Guzowski et al 2001;Messaoudi et al 2002;Bramham and Messaoudi 2005;Soule et al 2006;Wibrand et al 2006). Thus, an increase in bdnf mRNA in the cortex may drive the arc response by initiating translation of newly synthesized arc mRNA in activated dendritic spines (Yin et al 2002;Ying et al 2002). In addition, BDNFinduced arc synthesis during extinction learning may help drive synaptic consolidation to completion (Bramham and Messaoudi 2005;Haubensak et al 1998;Lessmann 1998), a mechanism likely necessary to consolidate learned associations into long-term memory.…”
Section: Functional Significance Of Gene Expression Changesmentioning
confidence: 99%
“…The dendritic localization and translation of the Arc mRNA has been extensively studied (Messaoudi et al, 2007;Rao et al, 2006;Steward et al, 1998;Steward and Worley, 2001;Yin et al, 2002;Ying et al, 2002), and BDNF was shown to increase dendritic Arc mRNA and protein levels in cultured cortical neurons (Rao et al, 2006). A role for Arc in LTP was shown in experiments with intrahippocampal infusion of antisense (AS) oligodeoxynucleotides to inhibit Arc protein expression, which impaired the maintenance phase of LTP without affecting its induction (Guzowski et al, 2000).…”
Section: Bdnf-induced Changes In the Neuronal Proteomementioning
confidence: 99%